Lobbying Bureaucrats: Delegation and Influence Under Alternative Political Structures - Morten Bennedsen; Sven E. Feldmann (Copenhagen Business School (CBS), Department of Economics, 2007)
This paper studies how interest group lobbying of the bureaucracy affects policy outcomes and how it changes the legislature's willingness to delegate decision-making authority to the bureaucracy. We extend the standard model of delegation to account for interest group influence during the implementation stage of policy and apply it to different institutional structures of government. The paper addresses the following questions: First, how does the decision to delegate change when the bureaucratic agent is subject to external influence? What cost does this influence impose on the legislative principal? Finally, how susceptible are policy choices to bureaucratic lobbying under different government structures? In answering these questions, the paper seeks to provide a comparative theory of lobbying and to explain the different patterns of interest group activity across political systems.
hdl:10398/7561
Keywords: G10; 330